2021
DOI: 10.1136/bmj.n973
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and self-harm in adult survivors of critical illness: population based cohort study

Abstract: Objective To analyse the association between survival from critical illness and suicide or self-harm after hospital discharge. Design Population based cohort study using linked and validated provincial databases. Setting Ontario, Canada between January 2009 and December 2017 (inclusive). Participants Consecutive adult intensive care unit (ICU) survivors (≥18 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 39 publications
4
36
0
1
Order By: Relevance
“…Joblessness is common, and nearly half of ICU survivors experience financial stress after hospital discharge [27]. The suicide ratio in PICS survivors is two times higher than non-ICU hospital survivors [117], and the support of their lives is essential. In addition to personal care, the impact on society also needs to be described.…”
Section: Future Directionsmentioning
confidence: 99%
“…Joblessness is common, and nearly half of ICU survivors experience financial stress after hospital discharge [27]. The suicide ratio in PICS survivors is two times higher than non-ICU hospital survivors [117], and the support of their lives is essential. In addition to personal care, the impact on society also needs to be described.…”
Section: Future Directionsmentioning
confidence: 99%
“…Among opioid naïve patients experiencing mechanical ventilation, 2.6% were found to have persistent opioid use after discharge, which was higher than matched non-ICU control patients (1.5%) [ 7 ]. Finally, more recent work from Ontario, Canada found that ICU survivors have higher rates of deliberate self-harm and suicide, as compared to matched non-ICU hospitalized patients [ 8 ]. Thus, in addition to the common physical and cognitive sequelae that they experience, survivors of critical illness are at increased risk of new mental health diagnoses, psychotropic medication use, substance misuse, deliberate self-harm, and suicide.…”
Section: Mental Health Morbidity Among Icu Survivorsmentioning
confidence: 99%
“…Delirium is common, and may be associated with a number of mental health sequelae, namely PTSD [ 13 ]. While there has been disagreement on the association between ICU length of stay or severity of illness with mental health morbidity [ 5 , 6 , 8 , 13 ], a number of studies have shown that incidence of new mental health diagnoses is associated with invasive procedures, such as mechanical ventilation [ 5 ]. Similarly, invasive mechanical ventilation and renal replacement therapy were prognostic for self-harm and suicide among ICU survivors [ 8 ].…”
Section: Prediction and Mitigation Of Riskmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 These issues are not benign and cause significant strain for the individual, such as an inability to return to employment and increased rates of suicide and self-harm. 8 9 …”
Section: Introductionmentioning
confidence: 99%